A Novel Method for Intraoral Access to the Superior Head of the Human Lateral Pterygoid Muscle. (15th May 2014) - Oliveira, Aleli Tôrres; Camilo, Anderson Aparecido; Bahia, Paulo Roberto Valle; Carvalho, Antonio Carlos Pires; DosSantos, Marcos Fabio; da Silva, Jorge Vicente Lopes; Monteiro, André Antonio
Abstract : Background. The uncoordinated activity of the superior and inferior parts of the lateral pterygoid muscle (LPM) has been suggested to be one of the causes of temporomandibular joint (TMJ) disc displacement. A therapy for this muscle disorder is the injection of botulinum toxin (BTX), of the LPM. However, there is a potential risk of side effects with the injection guide methods currently available. In addition, they do not permit appropriate differentiation between the two bellies of the muscle. Herein, a novel method is presented to provide intraoral access to the superior head of the human LPM with maximal control and minimal hazards. Methods. Computational tomography along with digital imaging software programs and rapid prototyping techniques were used to create a rapid prototyped guide to orient BTX injections in the superior LPM. Results. The method proved to be feasible and reliable. Furthermore, when tested in one volunteer it allowed precise access to the upper head of LPM, without producing side effects. Conclusions. The prototyped guide presented in this paper is a novel tool that provides intraoral access to the superior head of the LPM. Further studies will be necessary to test the efficacy and validate this method in a larger cohort of subjects.